Engineering Performance and Mechanism of Alkali-Activated Ground Granulated Blast Furnace Slag–Zeolite Powder Grouting Materials - Longni Wang; Hongyuan Fu; Qianfeng Gao; Jintao Luo; Jing Tang; Jianping Song; Youjun Li; Guangtao Yu (Applied Sciences)
Geopolymer-based grouting materials often have a higher early strength, better durability, and lower environmental impact than those of traditional cement-based grouts. However, existing geopolymer grouts face common challenges such as rapid setting and low compatibility with treated substrates. This study develops a new grouting material using industrial byproducts to overcome these limitations while optimizing performance for reinforcing silty mudstone slopes. The base materials used were ground granulated blast furnace slag (GGBFS) and zeolite powder, with calcium lignosulphonate (CL) serving as the retarding agent and NaOH as the alkali activator. The investigation focused on the effects of the mix ratio and water–binder ratio on the setting time, flowability, bleeding rate, concretion rate, and compressive strength of the new grouting material. Scanning electron microscope (SEM) and X-ray diffraction (XRD) analyses were employed to examine the action mechanism of the material components in the slurry. The one-factor standard deviation method and Grey Relational Analysis (GRA) were used to assess the influence of each material component on the slurry performance indices and the correlation between each performance index and its optimal mix ratio. Subsequently, the optimal mix ratio of the new grouting material was ascertained. The results indicate that the setting time is positively correlated with the zeolite powder and CL dosages and the water–binder ratio, while it is inversely related to the NaOH dosage. The flowability is significantly enhanced with increasing zeolite powder and NaOH dosages, but decreases at a higher CL dosage and water–binder ratio. This insight is crucial for optimizing the workability of the grouting material under various conditions. The optimal ratio of the grout is zeolite powder:GGBFS:CL:NaOH = 30:70:5:7, with a water–binder ratio of 0.6. Compared to existing commercial grouting materials, the compressive strength of this new grout is comparable to that of silty mudstone. This significantly reduces the problem of stress concentration at the grout–rock interface due to strength differences, thus effectively reducing the risk of secondary cracking at the interface. These findings provide a new material solution for grouting and repairing fractured silty mudstone slopes.